EFFECTIVENESS OF PARENTAL HOLDING TERAPHY AND MUSICAL TERAPHY TO REDUCE PAIN SCALES IN INFANT DURING MEASLES IMMUNIZATION - Fitri Wahyuni; Ulfa Suryani (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Background: Cases of measles in Indonesia are among the 10 biggest diseases that occur in children aged 29 days - 4 years. At the age of 9 months the infant must get immunizations that can be given by subcutaneous which can give the baby pain experience.Objectives: The purpose of this study was to determine the effectiveness of parental holding therapy and music therapy to reduce pain scales in the infants during measles immunization.Methods: This type of research is quasy experiment with the pretest and posttest approach without control of the design group. The sampling technique in this study used a